Los impuestos sobre las ganancias y su incidencia en los resultados económicos de la empresa internegocios de hierro S.A. cantón Quevedo, año 2012. - Ycaza Salazar, Carlos Augusto (2015)
This thesis was aimed at establishing the relationship of economic performance on the income tax of the company Internegocios Iron SA, Quevedo Canton, 2012, whose purpose was to verify the recovery of deferred tax items affecting identify taxable profit, make the clearance of consignments tax base and taxable / deductible temporary differences. The objectives of this study were: to examine the internal control accounting treatment for income taxes of the company, know that method is used in accounting for deferred taxes, analyze the application of the tax base for tax calculation deferred, and check the temporary differences that apply to deferred taxes….